Establishing factors affecting tax morale of the millennials in the gig economy / Farah Nabila Md Fadzil - Farah Nabila , Md Fadzil (2020)
The lack of clear conceptual framework and understanding of the tax morale in the gig economy is due to the contemporary literature being sparse. Considering the development of the gig economy, the purpose of this study is to provide insights on the factors affecting tax morale of those working in the gig economy. Data was then collected from millennials working in the gig economy through a questionnaire survey and analysed using second generation multivariate analysis, known as PLS-SEM. Taking into account self-efficacy and social cognitive theory as theoretical foundation, the findings reveal that while the extent of the dependency on the gig economy has a positive relationship on tax morale, level of education is negatively correlated. On the other hand, perceptual moral attentiveness is positively correlated with tax morale, unlike reflective moral attentiveness. Further, the findings of this study elaborate on the possibilities, limitations and how the findings can be implemented in practice especially in redesigning legal form. No earlier study has examined factors affecting tax morale in the context of the gig economy and this shall be beneficial to tax authorities and policymakers. This study also offers insights into the multidimensional aspect of tax morale of millennials working in the area of the gig economy.